Statin use and Vital Organ Failure in Patients With Asthma–Chronic Obstructive Pulmonary Disease Overlap: A Time-Dependent Population-Based Study - Yeh, Jun-Jun; Syue, Shih-Huei; Lin, Cheng-Li; Hsu, Chung Y.; Shae, Zonyin; Kao, Chia-Hung (Frontiers in Pharmacology, 2019)
Objective: The effects of statins on the risk of hepatic, renal, respiratory, and heart failure among patients with asthma–chronic pulmonary disease overlap (ACO) have not been reported. Design: time-dependent population-based study Setting: Patient data from 2000 to 2010 were retrieved from the Taiwan National Health Insurance Research Database. Patients: We divided patients with ACO into cohorts of statin use (N = 1211) and nonuse (N = 7443). Measurements and Main Results: The cumulative incidence rates of hepatic, renal, respiratory, and heart failure were analyzed through Cox proportional regression analysis with time-dependent variables. After adjustment for multiple confounding factors, including age, sex, comorbidities, and medications (statins, inhaled corticosteroid [ICS], or oral steroid [OS]), the adjusted hazard ratios (aHRs) (95% confidence intervals [CIs]) for hepatic, renal, respiratory, and heart failures were 0.50 (0.40–0.64), 0.49 (0.38–0.64), 0.61 (0.27–2.21), and 0.47(0.37–0.60), respectively. The aHRs (95% CIs) for statin use with [ICS, OS] for hepatic, renal, and heart failure were [0.36 (0.20–0.66), 0.52 (0.39–0.70)]; [0.82 (0.51–1.34), 0.46 (0.33–0.63)]; and [0.66 (0.40–1.07), 0.48 (0.37–0.64)], respectively. Conclusions: The ACO cohort with statin use exhibited the lower risk of hepatic, renal, and heart failure than any other cohort, regardless of age, sex, comorbidities, or ICS or OS use. Regarding the combined use of statins and ICS, the risks of hepatic failure were lower. For the combined use of statins and OS, the hepatic, renal and heart failure were less frequent.